Mechanisms of Arrhythmogenicity in Hypertrophic Cardiomyopathy: Insight From Non-invasive Electrocardiographic Imaging - Perez-Alday, Erick A.; Haq, Kazi T.; German, David M.; Hamilton, Christopher; Johnson, Kyle; Phan, Francis; Rogovoy, Nichole M.; Yang, Katherine; Wirth, Ashley; Thomas, Jason A.; Dalouk, Khidir; Fuss, Cristina; et al. (Frontiers in Physiology, 2020)
Background—Mechanisms of arrhythmogenicity in hypertrophic cardiomyopathy (HCM) are not well understood. Objective—To characterize an electrophysiological substrate of HCM in comparison to ischemic cardiomyopathy (ICM), or healthy individuals. Methods—We conducted a prospective case-control study. The study enrolled HCM patients at high risk for ventricular tachyarrhythmia (VT) (n=10; age 61±9 y; left ventricular ejection fraction (LVEF) 60±9%), and three comparison groups: healthy individuals (n=10; age 28±6 y; LVEF>70%), ICM patients with LV hypertrophy (LVH) and known VT (n=10; age 64±9 y; LVEF 31±15%), and ICM patients with LVH and no known VT (n=10; age 70±7y; LVEF 46±16%). All participants underwent 12-lead ECG, cardiac CT or MRI, and 128-electrode body surface mapping (BioSemi ActiveTwo, Netherlands). Non-invasive voltage and activation maps were reconstructed using the open-source SCIRun (University of Utah) inverse problem-solving environment. Results—In the epicardial basal anterior segment, HCM patients had the greatest ventricular activation dispersion [16.4±5.5 vs. 13.1±2.7 (ICM with VT) vs. 13.8±4.3 (ICM no VT) vs. 8.1±2.4 ms (Healthy); P=0.0007], the largest unipolar voltage [1094±211 vs. 934±189 (ICM with VT) vs. 898±358 (ICM no VT) vs. 842±90 µV (Healthy); P=0.023], and the greatest voltage dispersion [median(interquartile range) 215(161-281) vs. 189(143-208) (ICM with VT) vs. 158(109-236) (ICM no VT) vs. 110(106-168)µV (Healthy); P=0.041]. Differences were also observed in other endo-and epicardial basal and apical segments. Conclusion—HCM is characterized by a greater activation dispersion in basal segments, a larger voltage, and a larger voltage dispersion through LV.